Function and distribution of neuronal high-affinity IgE receptors (FcεRI) - Song, Jiheon (My University, 2012)
Background
IgE antibodies have high antigen specificity and are the hallmark biomarkers of allergy. IgE binds to high-affinity IgE receptors, known as FcεRI, which are expressed especially on mast cells and basophils. In allergic individuals, antigen binding to IgE that is associated with FcεRI leads to crosslinking of adjacent receptors and subsequently to cell activation, degranulation and/or secretion of bioactive molecules. These molecules together cause minor local tissue reactions such as oedema or itch, but also can cause major systemic reactions such as hypotension, cardiac and respiratory distress or even laryngeal swelling and death. The role of the nervous system in these reactions is usually thought of as secondary. However, in recent years there have been a number of studies suggesting the expression of FcεRI on neurons, opening the possibility that nerves are directly involved in antigen-specific responses and making a previously unrecognized contribution to allergic disease.
Based on these previous observations regarding neuronal FcεRI, the current study employed both in vivo and in vitro approaches with the following objectives:
To confirm the presence of FcεRI on peripheral nerves and demonstrate that they are functionally active under different conditions of IgE sensitization.
To examine the pathways involved in neuronal activation by IgE bound to FcεRI and compare and contrast these to those already established for mast cells and basophils.
Methods and Results
A potential role of neuronal FcεRI in the IgE-dependent allergen avoidance behaviour of sensitized mice presented with antigen in sucrose solution was assessed based on published evidence for the involvement of peripheral nerves in this response.
Chimeric mice with a wild-type nervous system but lacking FcεRI on hematopoietic cells including mast cells and basophils, failed to exhibit aversive behaviour, whereas mice with FcεRI-bearing hematopoietic cells demonstrated the normal aversive response confirming that FcεRI expression on mast cells is necessary for development of allergen avoidance. While immunohistochemical staining could detect IgE bound to mast cells in tissue samples, no IgE was detected on nerves where the nerves were identified by using a pan-neuronal marker, PGP 9.5, in the intestine of either normal or passively sensitized C57BL/6 and BALB/c mice. Similarly, traditional FACS analysis clearly identified FcεRI on cultured mast cells, but these methods provided no evidence for expression of FcεRI or IgE binding on superior cervical ganglion (SCG) and dorsal root ganglion (DRG) neurons in culture.
To determine evidence for functional FcεRI on neurons in vitro, intracellular calcium increase was assessed as a measure of cell activation following sensitization and antigen challenge. Using both microscopy and FACS analysis, calcium fluorophore (Fluo-3, AM) increase could be detected in SCG or DRG that were activated with the calcium ionophore A23187 but not following antigen challenge.
Summary: The current study found no evidence for the presence of the FcεRI on neurons in situ or their sensitization by IgE actively or passively using several different approaches both in tissues and cultured SCG or DRG neurons. Possible explanations for the resultant discrepancy with previously published works are discussed.
Keywords: IgE; FcεRI; SCG; allergy; high-affinity IgE receptor; Molecular and Cellular Neuroscience; Molecular and Cellular Neuroscience